Integratie. [Met bijdrn van N.E.H. van Esveld, R. Stolzenburg, B. ter Borch e.a. Met voorw. van J.M.P. Bongaerts]
Nammogram. Personeelsblad van de N.V. Nederlandse Aardolie Maatschappij. 6e jrg., 1965, nr 14 en 15, 8 oktober.